Optimization of pharmacotherapy of COPD patients using EURO FORTA and STOPP/START criteria - E. A. Orlova (Izdatelstvo OKI, 2023)
Relevance. Polypharmacy in taking medicines as one of the main consequences of comorbid pathology is a well-known risk factor for adverse drug reactions (ADRs). ADRs are often the cause of worsening disease course, disability, and mortality, especially in the elderly. This trend necessitates optimization of pharmacotherapy used in elderly patients using analytical algorithms for safety assessment. Objective. To analyze the safety of antibacterial and bronchodilator pharmacotherapy in COPD patients over 65 years old by means of comparative analysis of the data obtained according to EURO FORTA system methods and STOPP/START criteria. Methods. To conduct the study, a patient portrait was made on the basis of inpatient records data with the determination of Charlson and ADO indices. The influence of the severity of COPD course and comorbid pathology on polypharmacy was determined using the Spearman correlation coefficient (r). Evaluation of efficiency in the application of EURO FORTA and STOPP/START analytical criteria was carried out using a comparative analysis method. Statistical processing of the obtained data was performed using the StatPlus 7.0 program. Results. 113 inpatient records of elderly patients with moderately severe and severe COPD were studied. On the background of high severity of comorbid pathology, polypharmacy was observed in 102 patients (90.2%). The application of EURO FORTA and STOPP/START analytical tools in the analysis of bronchodilator and antibacterial therapy revealed 71 prescriptions of potentially unrecommended drugs in 61 (53,9%) patients. Conclusion. The analysis showed a high rate of prescribing drugs with significant risk in elderly patients. The conducted comparative analysis of two analytical tools for evaluation of the used pharmacotherapy EURO FORTA and STOPP/START demonstrated the necessity of their joint use to achieve the best results in ensuring safety of treatment of elderly patients, as they successfully complement each other.